(8-Bromo-2-hydroxy-7-methoxy-1-naphthyl)(4-chlorobenzoyl)methanone - Noriyuki Yonezawa; Keiichi Noguchi; Atsushi Nagasawa; Kosuke Nakaema; Ryosuke Mitsui (Acta Crystallographica Section E, 2010)
In the title compound, C18H12BrClO3, the naphthalene ring system and the benzene ring make a dihedral angle of 82.18 (9)°. The conformation around the central C=O group is such that the C=O bond vector forms a larger angle to the plane of the naphthalene ring system than to the plane of the benzene ring, viz. 60.91 (16)° versus 13.94 (16)°. In the crystal structure, two π–π interactions formed between the naphthalene ring systems [centroid–centroid distances of 3.8014 (13) and 3.9823 (13) Å] and intermolecular O—H...O and C—H...O hydrogen bonds are present.